The Scene of its Achievement: History, Tourism, and the Raising of HMS Nancy - Stubbs, Todd (Ontario History)

(untitled) (The Ontario Historical Society, 2012)
This article examines the debate over the ownership and preservation of an artefact of the War of 1812-14: the wrecked hull of the schooner HMS Nancy, which was discovered and raised at the mouth of the Nottawasaga River in Wasaga Beach, Ontario, in the summer of 1925. The discovery precipitated a vigorous struggle for control of the artefact that pitted local historical enthusiasts and politicians against the government of Ontario and its representatives. The crux of the debate concerned where best to store and house the hull. The government initially intended to remove the Nancy’s remains to Toronto where, officials argued, the vessel could best enjoy the status of a truly national icon, while an organized group from the Nottawasaga region charged that the artefact should remain in the place it perished as the best way to honour its historical significance as a symbol of British-Canadian nationhood and to make use of its value as a tourist attraction. The events highlight the ways in which Ontarians conceptualized their history and historical meanings of place during a period of tremendous social, cultural, and economic change.